2002
DOI: 10.1034/j.1600-0420.2002.800605.x
|View full text |Cite
|
Sign up to set email alerts
|

Macular holes: classification, epidemiology, natural history and treatment

Abstract: ABSTRACT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
124
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(130 citation statements)
references
References 97 publications
3
124
0
3
Order By: Relevance
“…According to the classification of macular holes, the posterior hyaloid is attached in stages 1-3 and is detached in stage 4 [20,21]. Usually, the posterior hyaloids is also detached in idiopathic ERMs [43,44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the classification of macular holes, the posterior hyaloid is attached in stages 1-3 and is detached in stage 4 [20,21]. Usually, the posterior hyaloids is also detached in idiopathic ERMs [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…The study setting was at our clinic, where both males and females, over 50 years of age, with visual deterioration related to full-thickness macular hole (Stages 2-4) [1,20,21] or macular pucker were included. Exclusion criteria were any other retinal disorders, glaucoma, optic atrophy, and visual field defects.…”
Section: Methodsmentioning
confidence: 99%
“…23 Moreover, Haouchine et al 5 reported that the initial structural feature was an intrafoveolar spilt occupying the inner retinal layers. This commonly accepted hypothesis of an inner cyst (stage 1-A MH) progressing to stage 1-B MH following an outer segment expansion [4][5][6][7][8][9][10][11] was questioned by Takahashi et al, 3,24 suggesting that the foveolar detachment of the COST line seen on SD-OCT might represent the yellow spot seen clinically in the very early stages of MH. In the present study 7 out of 10 patients who developed FTMH (in the initially normal fellow eye) demonstrated a clinically apparent yellow spot.…”
Section: Discussionmentioning
confidence: 99%
“…This may evolve into stage 1-B MH, whereby the posterior expansion of the pseudocyst creates a disruption of the outer retinal layer with an exposed retinal pigment epithelium and an intact roof. [4][5][6][7][8][9][10][11] This stage has been recently redefined as a vitreomacular traction that can be further subclassified by size of the adhesion into focal (r1500 mm) or broad (41500 mm). 12 Several questions remain unanswered with regards to the initial processes and morphological characteristics of the foveal microstructure in stage 1-A MH.…”
Section: Introductionmentioning
confidence: 99%
“…Common symptoms are metamorphopsia and blurring of vision, which was described as central scotoma in stage 4. However, in the initial stages, the patient may be asymptomatic (la Cour & Friis 2002).…”
Section: Case Reportmentioning
confidence: 99%